2023
DOI: 10.1212/wnl.0000000000207375
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcomes in Patients Exposed to OnabotulinumtoxinA Treatment

Abstract: Employee of AbbVie and receives salary and stock/stock options as compensation. L. Parker: Employee of AbbVie and receives salary as compensation. A. Ukah: Employee of AbbVie and receives salary and stock/stock options as compensation. L. Radulian: Employee of AbbVie and receives salary and stock/stock options as compensation and is a PhD student at the University of Medicine and Pharmacy. M.R.P. Elmore: Employee of AbbVie and receives salary and stock/stock options as compensation. L. Yedigarova: Former emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Spontaneous abortion and fetal defects have been reported with onabotulinumtoxinA treatment. 30 , 31 A recent 29-year retrospective study of the Allergan safety database reviewed the pregnancy outcomes of 397 mothers worldwide, a majority of whom ( n = 202 of the 242 pregnancies where dosage was reported) were exposed to <200 U of onabotulinumtoxinA during or within 3 months prior to pregnancy. 31 Of the 195 pregnancies that were recorded prospectively, 77.2% resulted in live births.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous abortion and fetal defects have been reported with onabotulinumtoxinA treatment. 30 , 31 A recent 29-year retrospective study of the Allergan safety database reviewed the pregnancy outcomes of 397 mothers worldwide, a majority of whom ( n = 202 of the 242 pregnancies where dosage was reported) were exposed to <200 U of onabotulinumtoxinA during or within 3 months prior to pregnancy. 31 Of the 195 pregnancies that were recorded prospectively, 77.2% resulted in live births.…”
Section: Discussionmentioning
confidence: 99%
“…During lactation, they are considered a safe option, but it is recommended to monitor for anticholinergic symptoms like dry mouth or constipation [ 74 , 84 ]. Lastly, onabotulinumtoxinA is not expected to enter the systemic circulation or to transfer to breast milk due to its high molecular weight, and retrospective studies have not observed an effect on pregnancy outcomes, but further studies are warranted to assess its safety [ 85 , 86 ].…”
Section: Introductionmentioning
confidence: 99%